AN EARLY EIGHTEENTH CENTURY TREATMENT FOR EQUINE BOT FLY - Duffin, Christopher (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2024)
This paper presents brief comments on an early modern treatment for infestation of horses by bot fly (probaby Gasterophilus intestinalis). The Scottish author and physician, Martin Martin (c. 1660-1718) records the rural Gaelic practise of treating diseased animals using water in which Jurassic belemnites, probably belonging to the genus Megateuthis and collected from Bajocian rocks on the eastern shores of the Isle of Skye, had been steeped. This means of treatment is something of an outlier in the range of medicinal uses of belemnites, and the philosophy behind it is not clear.
Keywords: materia medica, Scotland, Oestridae, bot fly, belemnite, Megateuthis